2020
DOI: 10.1044/2020_ajslp-20-00163
|View full text |Cite
|
Sign up to set email alerts
|

Assessment, Diagnosis, and Treatment of Dysphagia in Patients Infected With SARS-CoV-2: A Review of the Literature and International Guidelines

Abstract: Purpose Speech-language pathologists are playing a crucial role in the assessment and management of patients infected with severe acute respiratory syndrome coronavirus 2. Our goal was to synthesize peer-reviewed literature and association guidelines from around the world regarding dysphagia assessment and management for this specific population. Method A review of publications available in the PubMed database and official guidelines of international gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 69 publications
0
46
0
Order By: Relevance
“…The current review found a lack of consensus, high risk of selection bias and focused only on risk of infection based on previously-identified AGPs in the literature [15]. A similar trend was identified in a recent review exploring dysphagia and COVID-19; finding that no highquality scientific papers had been published to guide the recommendations being advised of clinicians globally [16]. This dysphagia paper reviewed only three articles which specifically…”
Section: Comparison With Other Studiesmentioning
confidence: 53%
See 1 more Smart Citation
“…The current review found a lack of consensus, high risk of selection bias and focused only on risk of infection based on previously-identified AGPs in the literature [15]. A similar trend was identified in a recent review exploring dysphagia and COVID-19; finding that no highquality scientific papers had been published to guide the recommendations being advised of clinicians globally [16]. This dysphagia paper reviewed only three articles which specifically…”
Section: Comparison With Other Studiesmentioning
confidence: 53%
“…Many of these tasks also occur commonly in healthcare settings and daily face-to-face societal interactions. The Royal College of Speech and Language Therapists (RCSLT) [15] and an additional speech pathology research group [16] have respectively produced reviews of the literature regarding COVID-19 and dysphagia; however to date, no research has been conducted to explore the aerosol transmission risk associated with COVID-19 in other areas of SLP clinical practice. As COVID-19 has been found to spread via aerosols generated during such respiratory activities as breathing, speaking, and coughing, SLPs appear to be at a particularly high risk of disease contraction when working with COVID-positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are still no scientific articles that offer specific disease and recovery profiles for patients with dysphagia and COVID-19 (Vergara et al, 2020). So too, are there more questions than answers when considering the consistencies and inconsistencies (and consistent inconsistencies!)…”
Section: Discussionmentioning
confidence: 99%
“…We recommend screening for OD in all COVID-19 hospitalised patients, with the diagnosis of OD made in a timely manner and based on clinical methods such as the Volume-Viscosity Swallow Test (V-VST). Treatment should be focused on compensatory strategies comprising postural management, thickening of fluids and the use of texture modified foods to provide a safe consistency in line with the European [ 23 ] and international guidelines [ 24 ].…”
Section: Focus On the Role Of Nutrition In Recovery From The First Day Of Hospital Admissionmentioning
confidence: 99%